Common cis-regulatory variation modifies the penetrance of pathogenic SHROOM3 variants in craniofacial microsomia - Zhu, Hao; Zhang, Jiao; Rao, Soumya; Durbin, Matthew D.; Li, Ying; Lang, Ruirui; Liu, Jiqiang; Xiao, Baichuan; Shan, Hailin; Meng, Ziqiu; Wang, Jinmo; Tang, Xiaokai; et al. (Genome Research, 2025)
Pathogenic coding variants have been identified in thousands of genes, yet the mechanisms underlying the incomplete penetrance in individuals carrying these variants are poorly understood. In this study, in a cohort of 2009 craniofacial microsomia (CFM) patients of Chinese ancestry and 2625 Han Chinese controls, we identified multiple predicted pathogenic coding variants in SHROOM3 in both CFM patients and healthy individuals. We found that the penetrance of CFM correlates with specific haplotype combinations containing likely pathogenic-coding SHROOM3 variants and CFM-associated expression quantitative trait loci (eQTLs) of SHROOM3 expression. Further investigations implicate specific eQTL combinations, such as rs1001322 or rs344131, in combination with other significant CFM-associated eQTLs, which we term combined eQTL phenotype modifiers (CePMods). We additionally show that rs344131, located within a regulatory enhancer region of SHROOM3, demonstrates allele-specific effects on enhancer activity and thus impacts expression levels of the associated SHROOM3 allele harboring any rare coding variant. Our findings also suggest that CePMods may serve as pathogenic determinants, even in the absence of rare deleterious coding variants in SHROOM3. This highlights the critical role of allelic expression in determining the penetrance and severity of craniofacial abnormalities, including microtia and facial asymmetry. Additionally, using quantitative phenotyping, we demonstrate that both microtia and facial asymmetry are present in two separate Shroom3 mouse models, the severity of which is dependent on gene dosage. Our study establishes SHROOM3 as a likely pathogenic gene for CFM and demonstrates eQTLs as determinants of modified penetrance in the manifestation of the disease in individuals carrying likely pathogenic rare coding variants.
10.1101/gr.280047.124